Volume 2A: Turbomachinery 2016
DOI: 10.1115/gt2016-56045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sweep on Performance of an Axial Compressor With Casing Grooves

Abstract: The need of increased stall margin is very high for aero gas turbine engines, as they operate under varied operating conditions. A number of different options are being used to increase the stall margin of gas turbine engines. Circumferential casing groove, in the compressor section of a gas turbine engine, is one of such methods. Incorporation of the grooves on the shroud increases the stall margin of the compressor, but this generally gives rise to loss of performance, such as efficiency and pressure ratio. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Numeca AutoGrid5Òversion 9.0-2 is used to generate structured mesh along with matching groove mesh. Details about numerical methodology are presented in already published work by current authors [21]. To obtain meshindependent results from the numerical analyses, mesh sensitivity study is carried out with three different mesh sizes (1.5 million, 2.5 million and 3.0 million).…”
Section: Numerical Methodology Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numeca AutoGrid5Òversion 9.0-2 is used to generate structured mesh along with matching groove mesh. Details about numerical methodology are presented in already published work by current authors [21]. To obtain meshindependent results from the numerical analyses, mesh sensitivity study is carried out with three different mesh sizes (1.5 million, 2.5 million and 3.0 million).…”
Section: Numerical Methodology Validationmentioning
confidence: 99%
“…Minimum skewness obtained for the final mesh is approximately equal to 20 degrees. The final mesh used for comparison of numerical results to experimental data is shown in figure 1 [21]. Ansys CFXÒversion 15.0 is used to carry out CFD analysis (single passage, steady, RANS).…”
Section: Numerical Methodology Validationmentioning
confidence: 99%
“…The results indicated that backward sweep rotor exhibited more stall warning time than zero sweep rotor. Goswami et al (2016) found that backward sweep increased stall margin and forward sweep increased the choked mass flow rate.…”
Section: Introductionmentioning
confidence: 98%